CAN EMPOWERING COMMUNITY PLATFORM - MAHILA AROGYA SAMITIS (MAS) UNDER NATIONAL URBAN HEALTH MISSION: STRENGTHEN THE DELIVERY OF PRIMARY HEALTHCARE SERVICES IN URBAN SLUMS? - Sudipta Basa; Madhulekha Bhattacharya; Ved Pal; V.K. Tiwari (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
The Astana Declaration was passed in 2018, forty years after Alma Ata, to provide a new momentum for strengthening Primary Healthcare (PHC) and to speed up the progress towards the Sustainable Development Goals (SDGs). One of the three pillars of PHC endorsed in Astana declaration was community empowerment. The strategies to strengthen community participation in health vary greatly. Unlike the rural areas the challenges are very different in urban areas. The healthcare services do not reach all urban poor settlements, especially the hidden pockets of urban poor and those that are not part of official lists. The weak linkage between slum communities and healthcare providers is a growing barrier to improve the health of the urban poor. The National Urban Health Mission launched in 2013, provides community platform in form of Mahila Arogya Samitis (MAS) to promote community participation in health activities in slum areas. In this article we present the need of empowering the MAS through simple interventions to address the healthcare needs of urban vulnerable population in slum areas.